IMAGING DIAGNOSIS—MAGNETIC RESONANCE IMAGING AND HISTOPATHOLOGICAL FEATURES OF A SKULL BASE CHORDOMA IN A CAT. Issue 2 (4th May 2016) - Brocal, Josep; Gamino, Virginia; Guevar, Julien; Gutierrez‐Quintana, Rodrigo; Marchesi, Francesco; Hammond, Gawain; Stalin, Catherine
Abstract : An 8‐year‐old domestic short‐haired cat was presented with anorexia, lethargy, ataxia and one episode of consciousness loss. A midline vertically orientated, biconcave, extra‐axial mass originating from the basioccipital bone was detected on magnetic resonance images of the head. The mass was T1W iso‐ to hypointense when compared with normal grey matter, T2W hyperintense with small areas of isointensity and heterogeneously enhanced with contrast. Multiple signal voids were observed on T2 * images. Histopathological evaluation confirmed a chordoma. To the authors' knowledge this is the first report of the imaging characteristics of a chordoma affecting the skull base in a cat.